Building a European database to gather multi-country evidence on active and latent TB screening for migrants. (March 2019) - Öhd, Joanna Nederby; Lönnroth, Knut; Abubakar, Ibrahim; Aldridge, Robert W.; Erkens, Connie; Jonsson, Jerker; Marchese, Valentina; Matteelli, Alberto; Menezes, Dee; Zenner, Dominik; Hergens, Maria-Pia
Highlights: E-DETECT TB, a European collaboration, collects screening data on active and latent TB for better evidence in future screening guidelines. E-DETECT TB aims to address the present lack of evidence concerning coverage, impact and cost-effectiveness in migrant TB screening. Through collaborative efforts, country-level screening is collated by using agreed key variables in a joint database. The project has successfully overcome considerable administrative, practical and legal challenges. Abstract: Background and aim: Screening for active and latent TB among migrants in low TB incidence countries may constitute an important contribution to TB elimination. E-DETECT TB, a European multi-county collaboration, aims to address the present lack of evidence on effectiveness of migrant TB screening by collating data in an international database and perform cross-country pooled and comparative analyses of screening coverage, results and linkage to care. Method: A database was established using migrant TB screening data from participating countries' national screening programs, national screening pilots and local research projects. All partner countries contributed to a common agreed protocol with standardized variables, pooling available numerator and denominator screening data from participating countries and sites. Results: All collaborating members drafted and agreed upon a data sharing accord as well as a protocol that clearly defined responsibilities and data governance principles. The database has been created and data transfer is ongoing. Conclusion: By persistence and focus the project has overcome considerable administrative, practical and legal challenges. This international collaboration provides greater power of analysis of harmonized data and thereby a unique opportunity to contribute migrant TB screening evidence. E-DETECT TB has started to invite other countries to contribute data to the database.